Females in Fetters: The Patriarchal World in Catherine Lim' S Selected Works - Ong, Siok Hong (2001)
This research seeks to explore the feminist views that filter through Catherine Lim's selected works: a collection of short stories and two novels. They capture the essence of feminism when she focuses on the dominant motif of servitude, suffering and subordination of women. Her abject stories of female suffering indicate her belief that women are the objects of oppression while men are the dominating subjects. She portrays women as victims of masculine power and authority. Much has been written by men on the representation of women in various texts. Therefore, it is refreshing to read texts written from a woman's perspective. Catherine Lim's creativity expresses the female experience, indicating her understanding of the emotions and struggles of women who are silenced, marginalised, and imprisoned in a patriarchal world. Her works deal with a wide range of issues: gender, class and culture, giving special focus on traditional Chinese society. Women are the losers, and the maids in bondage. In my opinion, Lim's feminist stance parallels those of leading feminists such as Virginia Woolf, Simone de Beauvoir and Kate Millett. This study offers a fascinating understanding of her narratives as a platform for social comment.